2009
DOI: 10.1111/j.1365-2850.2009.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Community psychiatric nursing in the Netherlands: a survey of a thriving but threatened profession

Abstract: The aim of this paper is to describe and analyse the Dutch community psychiatric nursing profession. In spite of their large numbers, estimated at 2900, Dutch community psychiatric nurses (CPNs) have contributed little to the international literature. The history of the profession reveals a relatively isolated development, resulting in few connections with nursing and mental healthcare research. Because of various developments in these fields, CPNs appear under threat. A survey design was used to administer a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The Delphi-variables were valid translations of data provided by community mental health experts in an extensive Delphi-study that has been reported on in detail before [15]. We have reason to believe that the results of our study also apply to CPNs outside the Netherlands since their role is relatively comparable worldwide [28]. They often, if not always in long-term care, work in close collaboration with psychiatrists.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The Delphi-variables were valid translations of data provided by community mental health experts in an extensive Delphi-study that has been reported on in detail before [15]. We have reason to believe that the results of our study also apply to CPNs outside the Netherlands since their role is relatively comparable worldwide [28]. They often, if not always in long-term care, work in close collaboration with psychiatrists.…”
Section: Discussionmentioning
confidence: 87%
“…The percentages of non-psychotic patients in long-term community mental health services are estimated between 20 and 50% [2125]. The key clinicians in long-term care for these patients often are community psychiatric nurses (CPNs), the most numerous professionals in community mental health in several countries [23, 26–28]. In this paper, we report on the perception of CPNs in community mental health care for non-psychotic chronic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Poor quality of life, severe suffering, high risk of suicidal behaviour, and high health care use (and corresponding costs) of this population without access to these psychotherapies, justify the development of a structured, easy-accessible intervention program. Our Collaborative Care Program may function as a valuable alternative for the relatively unstructured treatment which dominates the care as usual within existent community mental health care teams [16,17]. Within these CMHC teams nurses are the main care providers, although they are not always equipped to meet this responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…These patients often receive community mental health care (often referred to as a team: CMHC team), mostly provided by (community) mental health nurses [10,14]. The treatment delivered by CMCH teams is, however, not standardized and highly unstructured [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition a high volume of task-based activities and a lack of resources have long been highlighted as an everyday reality for hospital nurses (Currid, 2009;Nolan & Cushway, 1995). Comparably, community mental health nurses experience similar challenges, such as limited resources, high caseloads, and long waiting lists (Koekkoek et al, 2009;Keogh, Callaghan & Higgins, 2015). In order to accommodate a range of demands, the mental health nursing role may require nurses to have knowledge of a wide range of topics, and a flexible approach regarding how they undertake their work.…”
mentioning
confidence: 99%